Maternal Determinants of Stunting among Under-Five Children in the Service Area of Mata Public Health Center: A Qualitative Study - Listy Handayani; Hariati Lestari; Nurhijrianti Akib; Paridah; Sesy Dwi Prinita Jafarudin; Heni Delfita Maharani (Journal of Epidemiology and Health Science, 2026)
Background: Stunting remains a major public health issue in Indonesia, particularly in the service area of the Mata Public Health Center, which has reported the highest prevalence in Kendari City over the past three years.Objectives: This study aims to explore the maternal determinants contributing to stunting among children aged 2–5 years in the working area of Mata Public Health Center.Methods: A descriptive qualitative study was conducted in the Mata Public Health Center in July 2025. Five informants were selected through purposive sampling, consisting of two key informants (nutrition coordinator and MCH health worker) and three general informants (two mothers of stunted children and one mother of a non-stunted child). Data were collected through in-depth interviews guided by structured questions, then analyzed using coding, data categorization, and thematic interpretation.Results: Mothers demonstrated a generally adequate understanding of stunting, recognizing it as impaired growth influenced by nutrition, maternal health, and environmental hygiene. However, gaps emerged between perception and practice. Delayed first ANC visits (K1), limited awareness of the importance of early pregnancy monitoring, and inconsistent adherence to recommended ANC schedules reduced opportunities for preventive interventions. While IFA tablets were routinely distributed and monitored, consumption varied; some mothers adhered well, whereas others discontinued intake due to perceived side effects or insufficient quantities received.Conclusion: Maternal perceptions, ANC practices, and IF A supplementation behaviors significantly influence stunting outcomes in the Mata Public Health Center area. Strengthening maternal awareness through targeted education, improving early ANC engagement, and ensuring consistent monitoring of supplement adherence are essential strategies to reduce stunting prevalence.Keywords: Antenatal Care Visit, Determinant, IFA Consumption, Mother’s perception, Stunting